THE ANALYSIS OF SPEECH STYLE USED BY ELLEN DEGENERES IN ELLEN TALK SHOW - Eric Trio Putra; Rusdi Noor Rosa (English Language and Literature, 2019)
The aim of this study is analyse the speech style used by Ellen Degeneres in Ellen Talk Show. The title “Ellen Meets a 5-Year-Old Geography Expert”.Ellen Degeneres talk show is a TV show. The objectives of the study are to identify the speech styles used by the host and the guest in Ellen Degeneres Talk show and to identify the dominant speech styles used by the host and the guest on Ellen Degeneres Talk show.The findings of data is quantitative data, is it present in numbers and percentages. In analyzed the data, the writer read the transcript of conversation between Ellen and Nate and analyzed the data based on Joos theory. Then, the data has been presented in the form of a percentage table. The result of this research the writer found there are four speech style used by Ellen and Nate and once of category didn’t exist from this data (frozen style).This research is presenting of the data as main characters utterance containing speech styles. Based on Martin Joos theory (Frozen style, Formal style, Consultative style,Casual style and Intimate style) the writer found the speech styles used by Ellen and Nate, they are casual style that only occurs 11 times or 68%, consultative style that occurs 2 times or 13%, formal style that occurs 2 times or 13%, and intimate style that occurs once or 6%. The mostly used by Ellen and Nate occurs 11 times or 68%. Finally, the writer suggests the next researchers to explore more theories and the newest theory of speech styles.